2017
DOI: 10.15666/aeer/1503_13091321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Provenance and Climate on Xylem Anatomy of Haloxylon Ammodendron (C. A. Mey) Bunge in the Gurbantunggut Desert, China

Abstract: Abstract. Although Haloxylon ammodendron is widely distributed in desert regions of both Asia and Africa, the anatomical structure of its xylem is rarely reported. In this study, the differences in xylem anatomical characteristics among five provenances in the southern Gurbantunggut Desert were compared and the effects of climatic factors on anatomical features were analyzed. The results showed that the xylem responded to low precipitation by increasing ray density and ray height to improve the storage of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Haloxylon ammodendron is an important afforestation species in the arid desert region both in Asia and Africa. Previous studies have found that the cell wall of ray cells was obviously thickened in the xylem of H. ammodendron, and the wall thickness of the ray cell can be up to 2.85 µm ~ 3.08 µm, which is 3 ~ 6 times the thickness of axial parenchyma and is slightly higher than that of bre (2.64 µm ~ 2.97 µm) (Zhou and Gong 2017). Generally, ray tissue is composed of parenchyma cells, and the wall thickness of ray cells is much thinner than that of bre cells in most species (Plavcová and Jansen 2015).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Haloxylon ammodendron is an important afforestation species in the arid desert region both in Asia and Africa. Previous studies have found that the cell wall of ray cells was obviously thickened in the xylem of H. ammodendron, and the wall thickness of the ray cell can be up to 2.85 µm ~ 3.08 µm, which is 3 ~ 6 times the thickness of axial parenchyma and is slightly higher than that of bre (2.64 µm ~ 2.97 µm) (Zhou and Gong 2017). Generally, ray tissue is composed of parenchyma cells, and the wall thickness of ray cells is much thinner than that of bre cells in most species (Plavcová and Jansen 2015).…”
Section: Introductionmentioning
confidence: 86%
“…The climate and growth characteristics of H. ammodendron plantation in the sample area were described by Zhou and Gong (2017). At the end of June 2017, samples were taken in Jinghe (82°53′35″E,44°36′10″N) and Shihezi (86°14′44″E 45°00′34″N) Desert Research and Experimental Station, Shihezi University, in the Gurbantunggut Desert, Xinjiang, China.…”
Section: Sample Location and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, studies on the differences in provenances of forest trees were mainly focused on the growth traits (tree height, DBH) [ 6,7], physiological and biochemical traits [ 8], fitting growth model [ 9,10] and identification of molecular markers related to provenance [ 11]. However, there were few reports on the differences in RNA-Seq between provenances.…”
Section: Introductionmentioning
confidence: 99%
“…If ecologists or environmental scientists are talking about desert ecological research, then almost everyone is thinking about specific desert flora [1][2][3][4][5], fauna [6,7], or desertification itself as a consequence of climate change [8,9], or sand dunes-triggered disasters [10]. In fact, the importance of ecological research in deserts is far more general and wider.…”
Section: Introductionmentioning
confidence: 99%